Multi Chloroplast Genes for Species Identification in Bar-HRM Analysis of Taxonomical Complex Medicinal Plants Group (Zingiberaceae) - Sarawut Ounjai (Science Faculty of Chiang Mai University, 2019)
The economic importance of the herbal industry is increasing every year. As the herbal industry grows, consumer safety is one issue that cannot be overlooked. Buying herbal products poses a risk of acquiring counterfeited and adulterated products. Due to these issues, a reliable method to authenticate products is needed. Here DNA barcoding coupled with High Resolution Melting analysis (Bar-HRM), an emerging method for species identification, was developed. The four plastid barcodes were selected to test its efficiency in identifying the three closely related Zingiberaceae species. None of the primers derived from single locus can be discriminate all tested species whilst combination of two primer pairs proved to be more effective at discrimination. However, as DNA could be extracted from dried samples, the Bar-HRM here poses a great potential in applying for authentication of the tested Zingiberaceae herbal products in processed forms.